Theory of Mind Abilities and Deficits in Autism Spectrum Disorders. - Kimhi, Yael (Topics in Language Disorders)
Autism spectrum disorder (ASD) is a neurobiological disorder that significantly impairs children’s social interaction, verbal and nonverbal communication, and behaviors. Questions about theory of mind (ToM) deficits in ASD have generated a large number of empirical studies. This article reviews current studies of the relationship between ToM and ASD, including contributions to the understanding of social and academic manifestations of ASD. Several themes emerge: Enhanced language and verbal abilities facilitate better ToM understanding; implicit ToM elements that incorporate parallel processing pose more difficulties than explicit ones; and general and multimodal interventions are more effective than specific interventions. A brief overview is followed by a review of emerging research on the role of domain-general cognitive skills (executive function) and central coherence in the development of ToM. Next, a summary of studies addressing ToM across the development and social and academic manifestations is presented. The article ends with a critical review of ToM intervention studies, which suggests that generalization may be more likely to occur when ToM is targeted as part of broader sociocognitive interventions rather than as an isolated skill.